Assessing geopolitics as Nepal's national security challenge - Dhakal, Bikash (Unity Journal, 2020)
The increased geo-strategic interests and concerns of great powers have posed serious challenges to national security of Nepal. This article objectively analyzes the impacts of geopolitics on Nepal's national security. It intends to examine the National security within the framework of geopolitical rivalry. Geopolitics is rather a crucial external factor than the other internal factors of insecurity. Thus, this article attempts to justify how regional and global geopolitical developments challenge Nepal's national security. This article explains geopolitical factors that can pose threat and challenge to national security.